84.6k views
4 votes
F: x 5 – 3x. (a) Find f(–1). (b) Find f –1(x).

1 Answer

4 votes

Answer:


f(-1) = 8


f^(-1)(x) = (5)/(3) - (x)/(3)

Explanation:

Given


f(x) = 5 - 3x

Required


f(-1) and
f^(-1)(x)

Solving for f(-1)

Substitute -1 for x in
f(x) = 5 - 3x


f(-1) = 5 - 3(-1)


f(-1) = 5 + 3


f(-1) = 8

Solving for
f^(-1)(x)

Let y = f(x)


y = 5 - 3x

Interchange the position of x and y


x = 5 - 3y

Make y the subject of formula (add 3y to both sides)


3y + x = 5 - 3y + 3y


3y + x = 5

Subtract x from both sides


3y + x - x = 5 - x


3y = 5 - x

Divide through by 3


(3y)/(3) = (5)/(3) - (x)/(3)


y = (5)/(3) - (x)/(3)

Replace y with
f^(-1)(x)


f^(-1)(x) = (5)/(3) - (x)/(3)

User Andrew Butenko
by
6.1k points